A battery cell, a battery device, and an electric device

CN123018064APending Publication Date: 2026-10-30CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510558627.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-29
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]本申请的目的在于提供一种电池单体、电池装置和用电装置,旨在解决如何有效改善电池的循环性能的问题

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018064A_ABST
    Figure CN123018064A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of batteries, and provides a battery monomer, a battery device and a power utilization device. The battery monomer comprises a negative electrode sheet, the negative electrode sheet comprises a negative electrode current collector and a first negative electrode film layer arranged on at least one side of the negative electrode current collector, the first negative electrode film layer comprises a first negative electrode active material and a first conductive agent, the first negative electrode active material comprises a silicon-based material, and the first conductive agent comprises flaky graphite, and the aspect ratio of the flaky graphite is greater than or equal to 10. With the aid of the relative sliding between the flaky graphite layers, stress can be relieved, the silicon-based material is not prone to massive rupture and pulverization due to excessive stress after the negative electrode sheet undergoes multiple charging and discharging cycles, the negative electrode sheet is not prone to cracks and breakage due to the expansion and rebound of the silicon-based material, the overall integrity form and internal conductive network of the negative electrode sheet can be better maintained, and therefore the performance stability and cycle life of the battery are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of battery technology, and in particular relates to a battery cell, a battery device, and an electrical device. Background Technology

[0002] Rechargeable batteries, with their outstanding characteristics of being clean, environmentally friendly, and renewable, are finding increasingly wide applications and have been deeply integrated into many fields such as consumer electronics, electric vehicles, and energy storage. As the application scope of rechargeable batteries continues to expand, users are placing higher demands on battery cycle performance. However, the cycle performance of batteries on the market still falls short of expectations and urgently needs further optimization and improvement.

[0003] The above statements are for the purpose of providing background information in relation to this application only and do not necessarily constitute prior art. Summary of the Invention

[0004] The purpose of this application is to provide a battery cell, a battery device, and an electrical device, which aims to solve the problem of how to effectively improve the cycle performance of a battery.

[0005] To achieve the above-mentioned objectives, the technical solution adopted in this application is as follows:

[0006] In a first aspect, this application provides a battery cell including a negative electrode sheet, the negative electrode sheet including a negative current collector and a first negative electrode film layer disposed on at least one side of the negative current collector, the first negative electrode film layer including a first negative electrode active material and a first conductive agent, the first negative electrode active material including a silicon-based material, the first conductive agent including flake graphite, the aspect ratio of the flake graphite being greater than or equal to 10.

[0007] In this application, when the aspect ratio of flake graphite is greater than or equal to 10, it can exhibit a flat, sheet-like morphology. Therefore, due to its flat, sheet-like structure, the flake graphite can effectively fill the gaps between silicon-based material particles. Its larger flat surface increases the contact area with the silicon-based material, greatly improving the contact tightness and fit between the two. Simultaneously, the flakes of flake graphite with an aspect ratio greater than or equal to 10 have a larger contact area between the flakes, which significantly reduces the resistance to relative sliding between the flakes, significantly reducing the difficulty of relative sliding between the flakes, thus giving it the advantage of easy relative sliding.

[0008] During battery charging and discharging, silicon-based materials are prone to volume expansion due to the insertion and extraction of active ions, which in turn exerts compressive stress on the closely contacting flake graphite. Therefore, by utilizing the advantage of the relative slippage between flake graphite layers with an aspect ratio greater than or equal to 10, the concentrated stress generated by the expansion of silicon-based materials can be effectively dispersed over a wider area. Simultaneously, the sliding and rearrangement of the graphite layers greatly reduces the risk of excessive stress concentration in localized areas. Furthermore, the good flexibility of the graphite layers themselves allows them to absorb some stress during slippage, effectively alleviating the stress caused by particle expansion within the negative electrode, significantly reducing the degree of expansion of the negative electrode, and thus effectively improving the cycle life of the battery cell.

[0009] In some embodiments, the aspect ratio of the flake graphite is 10-160.

[0010] The aspect ratio of flake graphite is within the above range, which means that its extension scale in the two-dimensional plane is much greater than its thickness and its shape is extremely flat. This makes it easier for flake graphite to slip relative to each other when subjected to force. This is more conducive to improving the electrode rebound phenomenon caused by the volume expansion and contraction of silicon-based materials, reducing the expansion degree of the negative electrode, effectively improving the structural stability of the negative electrode, and thus greatly improving the cycle performance of the battery.

[0011] In some embodiments, the ratio of the particle size of the silicon-based material to the particle size of the flake graphite is 1:x, where 0.5 ≤ x < 1.

[0012] By rationally controlling the particle size ratio of silicon-based materials and flake graphite, the close contact between the two can be greatly promoted. In this way, the flake graphite, with its unique flake structure, is well distributed in the gaps between the silicon-based material particles.

[0013] In some embodiments, the particle size of the silicon-based material is 7μm-10μm, and the particle size of the flake graphite is 4μm-8μm.

[0014] The appropriate particle size of silicon-based materials makes their volume expansion and contraction relatively uniform. Flake graphite, with its suitable particle size, closely adheres to the silicon-based materials. Utilizing its own flat structure advantage, it fully exerts its buffering and stress dispersion effects when the volume of the silicon-based materials changes, effectively alleviating the rebound and expansion phenomena of the negative electrode sheet caused by stress concentration. This helps to improve the structural integrity of the negative electrode sheet and greatly enhances the cycle stability of the battery.

[0015] In some embodiments, the degree of graphitization of the flake graphite is 91%-98%.

[0016] When the degree of graphitization of flake graphite is within the above range, its flexibility is good. This allows flake graphite to effectively absorb and disperse stress when the volume change of silicon-based materials during charging and discharging, resulting in a more balanced stress distribution inside the negative electrode sheet. This reduces the risk of excessive stress accumulation in local areas, greatly improves the stability of the negative electrode sheet, and thus effectively extends the cycle life of the battery.

[0017] In some embodiments, the silicon-based material includes at least one of silicon oxides, silicon-carbon composites, and silicon alloys.

[0018] These silicon-based materials have a high specific capacity and can store more active ions.

[0019] In some embodiments, the mass percentage of silicon in the silicon-based material is 45%-60%.

[0020] When the mass percentage of silicon is within the above range, the advantage of silicon's high specific capacity can be better utilized to improve the energy density of the battery.

[0021] In some embodiments, the first conductive agent further includes a first dotted conductive agent, wherein the mass ratio of the first dotted conductive agent to the flake graphite is 1:(1-5).

[0022] The short-range electrical connections formed by the first point-like conductive agent work closely together with the medium-range electrical connections built by the flake-like graphite to create a more efficient conductive network within the negative electrode sheet. This significantly improves the electron transport rate, greatly reduces the overall resistance of the electrode, and optimizes the reaction kinetics within the battery. Thus, when the battery is charged, the large current can drive more active ions to embed into the silicon-based material at a faster rate, significantly shortening the charging time and effectively improving the battery's fast-charging performance.

[0023] In some embodiments, the first conductive agent further includes a linear conductive agent, and the mass ratio of the linear conductive agent, the first dot-shaped conductive agent and the flake graphite is 1:(4-6):(12-18).

[0024] The linear conductive agent connects the short-range region formed by the first point-like conductive agent and the medium-range region constructed by the flake-like graphite. In this way, after completing short-range and medium-range transport, electrons can quickly traverse the entire negative electrode along the linear conductive agent, achieving long-range, efficient electron transport within the negative electrode. This significantly improves electron transport efficiency, greatly optimizes the internal reaction kinetics of the battery, and thus effectively enhances the battery's fast-charging performance and cycle life.

[0025] In some embodiments, the linear conductive agent includes at least one of carbon nanotubes and carbon fibers.

[0026] These linear conductive agents have excellent conductivity, enabling electrons to be transported quickly, thereby improving the charging and discharging efficiency of the battery.

[0027] In some embodiments, the first dot-like conductive agent includes at least one of carbon black, superconducting carbon, acetylene black, Ketjen black, and carbon dots.

[0028] In some embodiments, the first negative electrode film layer further includes a first dispersant and a first binder. Based on the total mass of the first negative electrode film layer as 100%, the content of the first negative electrode active material is 80%-85%, the content of the first conductive agent is 10%-15%, the content of the first dispersant is 1%-1.5%, and the content of the first binder is 4%-6%.

[0029] By adjusting the content ratio of each component in the first negative electrode film layer, it is beneficial for each component to exert a synergistic effect. Specifically, an appropriate amount of the first negative electrode active material helps to improve the energy density of the battery; an appropriate amount of the first conductive agent can build a stable and efficient conductive network between the negative electrode active materials, greatly reducing electron transport resistance, significantly improving the battery charge and discharge rate, and meeting the fast charging requirements; an appropriate amount of the first dispersant helps the components to mix evenly and form a stable and uniform negative electrode film layer; and an appropriate amount of the first binder can tightly bond the components into a solid whole, giving the negative electrode sheet good mechanical strength, effectively reducing material shedding and pulverization, and extending the battery cycle life.

[0030] In some embodiments, the negative electrode sheet further includes a second negative electrode film layer, which is disposed between the first negative electrode film layer and the negative electrode current collector;

[0031] The second negative electrode film layer includes a second negative electrode active material, which includes a carbon-based material.

[0032] The lithium intercalation process of carbon-based materials involves relatively small volume changes and good flexibility. When distributed in the second negative electrode film layer, which is the side close to the negative electrode current collector, the carbon-based material can absorb and disperse the stress through its own deformation when the first negative electrode film layer is subjected to stress due to the expansion of silicon-based materials. This reduces the overall rebound of the negative electrode sheet, minimizes performance degradation caused by structural damage, and extends the battery cycle life.

[0033] In some embodiments, the thickness ratio of the first negative electrode film layer to the second negative electrode film layer is (0.6-1):1.

[0034] Silicon-based materials have strong lithium intercalation capabilities but relatively large volume expansion, while carbon-based materials exhibit relatively small volume changes and good conductivity during lithium intercalation. Therefore, by adjusting the thickness ratio of the two films, silicon-based and carbon-based materials can fully leverage their respective advantages, thereby improving the battery's charging speed, overall capacity, and cycle life.

[0035] In some embodiments, the second negative electrode film layer further includes a second conductive agent, a second dispersant, and a second binder. Based on the total mass of the second negative electrode film layer (100%), the content of the second negative electrode active material is 95%-97%, the content of the second conductive agent is 0.5%-1%, the content of the second dispersant is 1%-1.5%, and the content of the second binder is 2%-4%.

[0036] By adjusting the content ratio of each component in the second negative electrode film, it is beneficial for each component to exert a synergistic effect. An appropriate amount of second negative electrode active material can stably store active ions; an appropriate amount of second conductive agent can build a highly efficient conductive network, accelerate electron conduction, and improve the charge and discharge rate; an appropriate amount of second dispersant promotes the uniform distribution of each component; and an appropriate proportion of second binder firmly binds the other components, enhances the mechanical strength of the negative electrode sheet, improves the structural stability of the negative electrode sheet during charge and discharge, and improves the battery cycle performance and fast charging performance.

[0037] In some embodiments, the second conductive agent includes a second dot-shaped conductive agent.

[0038] The second point-like conductive agent can effectively fill the gaps between carbon-based material particles, thereby forming a good conductive path between the carbon-based materials and effectively reducing the overall resistance of the negative electrode. This makes the transfer of electrons within the electrode more efficient, thus significantly improving the battery's charge and discharge efficiency and effectively enhancing its fast-charging performance.

[0039] In some embodiments, the film resistance of the negative electrode is 0.002Ω-0.01Ω.

[0040] The negative electrode has a low resistance range, which reduces the resistance encountered by the current when it travels through the electrode, thus improving the charging and discharging efficiency of the battery.

[0041] Secondly, this application provides a battery device including multiple battery cells as described in the above embodiments.

[0042] Thirdly, this application provides an electrical device that includes multiple battery cells or battery devices according to the above embodiments. Attached Figure Description

[0043] Various other advantages and benefits will become apparent to those skilled in the art upon reading the detailed description of the preferred embodiments below. The accompanying drawings are for illustrative purposes only and are not intended to limit the scope of this application. Furthermore, the same reference numerals denote the same parts throughout the drawings. In the drawings:

[0044] Figure 1 This is an exploded view of the battery device provided in the embodiments of this application;

[0045] Figure 2 This is an exploded view of a single battery cell provided in an embodiment of this application;

[0046] Figure 3 A schematic diagram of one embodiment of an electrical device that uses a battery cell as a power source, as described in the present application.

[0047] Figure 4 Scanning electron microscope images of flake graphite provided for this application;

[0048] Figure 5 A scanning electron microscope backscattered electron image of the negative electrode sheet provided in Embodiment 1 of this application;

[0049] Figure 6 A scanning electron microscope image of the negative electrode sheet provided in Comparative Example 1 of this application;

[0050] Figure 7 A scanning electron microscope image of the negative electrode sheet provided in Embodiment 1 of this application;

[0051] Figure 8 The charging curves provided for Embodiment 1 and Comparative Example 1 of this application are shown.

[0052] Explanation of reference numerals in the attached figures:

[0053] 100. Battery device;

[0054] 10. Box body; 11. First box body; 12. Second box body;

[0055] 20. Battery cell modules;

[0056] 30. Battery cell, 31. Casing, 32. Electrode assembly, 33. Cover plate. Detailed Implementation

[0057] The embodiments of the technical solution of this application will now be described in detail with reference to the accompanying drawings. These embodiments are only used to more clearly illustrate the technical solution of this application and are therefore merely examples, and should not be used to limit the scope of protection of this application.

[0058] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the drawings are intended to cover non-exclusive inclusion.

[0059] In the description of the embodiments of this application, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly defined.

[0060] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.

[0061] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.

[0062] In the description of the embodiments of this application, the term "multiple" refers to two or more (including two), similarly, "multiple sets" refers to two or more (including two sets), and "multiple pieces" refers to two or more (including two pieces).

[0063] In this application, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.

[0064] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0065] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0066] Unless otherwise specified, all steps of this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order; for example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0067] The weights of the relevant components mentioned in the embodiments of this application can refer not only to the specific content of each component, but also to the proportional relationship between the weights of the components. Therefore, any scaling up or down of the content of the relevant components according to the embodiments of this application is within the scope disclosed in the embodiments of this application. Specifically, the mass described in the embodiments of this application can be a mass unit known in the chemical industry, such as μg, mg, g, or kg.

[0068] In this embodiment of the application, the battery cell can be a secondary battery, which refers to a battery cell that can be recharged to activate the active materials and continue to be used after the battery cell has been discharged.

[0069] The term "linear conductive agent" refers to conductive materials that exhibit a linear morphology at the microscopic scale, specifically conductive materials with an aspect ratio greater than 1000.

[0070] The term "dot conductive agent" refers to an agent that appears as dot-like particles in its microscopic morphology. These particles are typically approximately spherical or near-spherical in shape.

[0071] Silicon-based materials theoretically possess extremely high specific capacity, exceeding 4200 mAh / g, a significant advantage over the 372 mAh / g of traditional graphite anode materials. Due to its high specific capacity, silicon-based materials are considered the most promising anode active materials. However, silicon-based materials undergo significant volume expansion and contraction during charge and discharge. Taking lithium-ion batteries as an example, this repeated volume change can reach approximately 300%-400%, generating substantial stress on the anode sheet. If this stress is not effectively released, with increasing charge-discharge cycles, it can lead to particle breakage and pulverization of the electrode material, gradually destroying the electrode structure and ultimately causing rapid capacity decay, severely impacting the battery's cycle life.

[0072] To effectively address the expansion problem of negative electrode sheets caused by silicon-based materials, the inventors discovered that adding flake graphite to the silicon-based material system, utilizing its interlayer slip properties, can suppress the expansion of the silicon-based material. Therefore, this application uses flake graphite with an aspect ratio greater than or equal to 10 as a conductive agent. Its flat, flake-like morphology allows it to effectively fill the gaps between silicon-based material particles, and its larger surface area increases the contact area with the silicon-based material. Thus, when the silicon-based material expands during charging and discharging, the flake graphite, with its easy interlayer slippage, effectively disperses the concentrated stress generated by the expansion of the silicon-based material over a wider area, thereby significantly improving the battery cycle life.

[0073] The first aspect of this application provides a battery cell. Specifically, the battery cell of this application includes a positive electrode and a negative electrode. The negative electrode includes a negative current collector and a first negative electrode film layer disposed on at least one side of the negative current collector. The first negative electrode film layer includes a first negative electrode active material and a first conductive agent. The first negative electrode active material includes a silicon-based material, and the first conductive agent includes flake graphite with an aspect ratio greater than or equal to 10.

[0074] Because flake graphite has an aspect ratio greater than or equal to 10, it has a flat, sheet-like shape. In addition, its good flexibility allows flake graphite to fill the gaps between silicon-based material particles well. Its large flat surface can increase the contact area with silicon-based material particles, thereby greatly improving the tightness and fit between the two.

[0075] Furthermore, an aspect ratio greater than or equal to 10 significantly increases the contact area between the flakes of graphite. This increased contact area effectively reduces the resistance to relative slippage between the flakes. This reduced resistance directly leads to a significant decrease in the difficulty of relative slippage between the flakes, thus giving flake graphite the advantage of being easy to slip relative to each other.

[0076] During battery charging and discharging, silicon-based materials are prone to volume expansion due to the insertion and extraction of active ions, which in turn exerts compressive stress on the flake graphite in close contact with them. This application uses flake graphite sheets with an aspect ratio greater than or equal to 10. Leveraging the advantage of easy relative slippage between the layers, the concentrated stress generated by the expansion of the silicon-based material can be effectively dispersed over a wider area. Simultaneously, the sliding and rearrangement of the graphite sheets greatly reduces the risk of excessive stress concentration in localized areas. Furthermore, the graphite sheets themselves possess good flexibility, absorbing some stress during slippage, effectively alleviating the stress caused by particle expansion within the negative electrode sheet, significantly reducing the degree of expansion of the negative electrode sheet, and making the negative electrode sheet structure more stable. Based on this, this application utilizes the relative slippage between the flake-like graphite layers to alleviate stress, which prevents the silicon-based material from cracking and pulverizing due to excessive stress after multiple charge-discharge cycles. The negative electrode is also less prone to cracking and breakage due to the expansion and rebound of the silicon-based material. In this way, the overall integrity of the negative electrode and the internal conductive network can be well maintained, thereby effectively improving the performance stability and cycle life of the battery.

[0077] Based on this, this application utilizes the flat, sheet-like morphology of flake-like graphite sheets and the relative slippage between their layers to alleviate stress. This allows the silicon-based material of the negative electrode sheet to be less prone to excessive cracking and pulverization due to excessive stress after multiple charge-discharge cycles. The negative electrode sheet is also less likely to develop cracks and fractures due to the expansion and rebound of the silicon-based material. In this way, the overall integrity of the negative electrode sheet and the internal conductive network can be well maintained, thereby effectively improving the cycle life of the battery cell.

[0078] Furthermore, the large surface area of ​​flake graphite allows for extensive contact with silicon particles, enabling efficient electron transport between them and creating dense, continuous conductive channels between the silicon-based material particles. The interweaving of numerous flake graphite flakes further intricately links electron transport paths, forming a more complete and efficient conductive network. This reduces interfacial resistance, accelerates the migration of active ions, and allows them to pass through the interface more quickly, minimizing transport obstacles. This significantly improves battery charging efficiency, enabling rapid charging of large amounts of energy in a short time, thus exhibiting excellent fast-charging performance.

[0079] Thanks to the excellent flexibility and deformability of flake graphite, when silicon-based materials undergo volume expansion or contraction due to the insertion and extraction of active ions, flake graphite can adapt to this structural change through relative slippage and self-deformation, thereby improving the integrity of the conductive network. As a result, after multiple charge-discharge cycles, the electron transport rate inside the negative electrode can still remain at a high level, ensuring that the fast-charging performance of the battery does not significantly degrade due to long-term use, thus positively impacting the battery's long-term and stable fast-charging performance.

[0080] The aforementioned "aspect ratio" refers to the ratio of the maximum length (usually the dimension along the crystal sheet direction) to the average thickness perpendicular to the length direction on a two-dimensional plane of a flake-like graphite crystal.

[0081] In this application, the aspect ratio can be tested in the following ways:

[0082] First, the negative electrode sheet was cut into 6mm × 6mm dimensions. Using a Sigma 300 scanning electron microscope, a surface SEM image of the negative electrode sheet was obtained. From this SEM image, more than 20 flake-like graphite particles were randomly selected, and their lengths were measured and averaged to obtain the average length of the flake-like graphite particles in the electrode sheet.

[0083] Next, the negative electrode sheet was fixed on an ion polishing machine and cut at 7.5 kV for 30 minutes. Testing and observation were conducted using a Sigma 300 scanning electron microscope with energy dispersive spectroscopy. Similarly, more than 20 flake graphites were selected, and their thicknesses were measured and averaged to obtain the average thickness of the flake graphites in the electrode sheet.

[0084] Finally, following the steps described above, each of the 10 negative electrode sheets was tested, and the average length and thickness of the flake graphite contained in each sheet were calculated. The lengths and thicknesses of the 10 electrodes were then averaged to obtain the final average length and thickness. The ratio of the final average length to the average thickness is the aspect ratio of the flake graphite.

[0085] In some embodiments, the aspect ratio of the flake graphite is 10-160. Exemplary examples include typical but non-limiting values ​​such as 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, and 160.

[0086] The aspect ratio of flake graphite is within the aforementioned range, meaning that its extension scale in the two-dimensional plane is much greater than its thickness, and its shape is extremely flat. This not only makes it easier for flake graphite to fill the gaps between silicon-based material particles, but also makes it easier for relative slippage to occur under stress. Therefore, when the silicon-based material expands in volume due to charging and discharging, and applies pressure to the surrounding flake graphite, the flake graphite, with its advantage of large-area adhesion and its good interlayer relative slippage characteristics, disperses the concentrated stress to a larger area, effectively avoiding excessive stress accumulation in local areas, significantly suppressing the rebound phenomenon of the negative electrode sheet, improving the structural stability of the negative electrode sheet, and enabling the battery to exhibit excellent cycle life.

[0087] In some embodiments, the ratio of the particle size of the silicon-based material to the particle size of the flake graphite is 1:x, where 0.5 ≤ x < 1. As an example, the ratio of the particle size of the silicon-based material to the particle size of the flake graphite can be 1:0.5 or 1:x, where x can be typical but not limiting values ​​such as 0.55, 0.6, 0.7, 0.8, 0.9, 0.95, etc.

[0088] By rationally controlling the particle size ratio of silicon-based materials and flake graphite, the close contact between the two can be greatly promoted. In this way, the flake graphite, with its unique flake structure, is well distributed in the gaps between the silicon-based material particles, thus achieving close contact between the two.

[0089] The large-area, close contact between the particle surface of silicon-based materials and flake graphite not only creates a stable and continuous conductive path for electron conduction, thus significantly improving the charging and discharging efficiency of the battery and positively impacting its fast-charging performance, but also allows the interface between the two materials to effectively transfer and disperse stress when the silicon-based materials undergo volume changes due to charging and discharging. The flake graphite can fully utilize its flexibility and the relative slippage characteristics of its layers to effectively buffer the stress generated by the expansion or contraction of the silicon-based materials, suppress the rebound and expansion of the negative electrode sheet, and thus extend the cycle life of the battery.

[0090] In some embodiments, the particle size of the silicon-based material is 7 μm-10 μm, and the particle size of the flake graphite is 4 μm-8 μm. Exemplarily, the particle size of the silicon-based material can be typical but not limiting values ​​such as 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, and 10 μm, and the particle size of the flake graphite can be typical but not limiting values ​​such as 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, and 8 μm.

[0091] The optimal particle size matching between silicon-based materials and flake graphite facilitates the formation of a stable microstructure within the negative electrode. Specifically, the flake graphite effectively fills the spaces between silicon-based material particles, achieving a tight bond between the two. On one hand, the silicon-based material, with its suitable particle size, provides more active sites, facilitating the insertion and extraction of lithium ions. Meanwhile, the flake graphite, with its appropriate particle size, constructs high-speed transport channels for active ions. This synergistic effect significantly improves the migration efficiency of active ions within the negative electrode, dramatically accelerating the battery's charge and discharge process, drastically shortening charging time, and enabling the battery to exhibit excellent fast-charging performance. On the other hand, the relative slippage between the flake graphite layers effectively absorbs and disperses stress when the silicon-based material expands or contracts, reducing structural damage caused by stress concentration. This allows the battery to perform stable charge and discharge reactions, minimizing performance degradation.

[0092] The following methods can be used to determine the particle size of silicon-based materials and flake graphite in the negative electrode sheet:

[0093] Optical imaging tests such as SEM (scanning electron microscope) were performed on the negative electrode sheet. Five regions of silicon-based material and flake graphite with the same size and shape (the actual size is a square sampling area of ​​15μm by 30μm) were randomly selected from the same SEM image at 3k magnification for observation.

[0094] The particle size of each silicon-based material within a square sampling area is measured, where the particle size refers to the longest diameter of the particle. The particle sizes within the square sampling area are then averaged to obtain the average particle size, which is the particle size of the silicon-based material in that area. The particle sizes of the five areas are then averaged to obtain the particle size of the silicon-based material in the negative electrode. Finally, following the above steps, each of the ten negative electrode sheets is tested individually, and the particle sizes of the ten electrodes are averaged to obtain the particle size of the silicon-based material.

[0095] The particle size of each flake graphite within a square sampling area is measured, where the particle size refers to the longest diameter of the particle. The particle sizes of the flake graphite within the square sampling area are then averaged to obtain the average particle size, which is the particle size of the flake graphite in that region. The particle sizes of the five regions are then averaged to obtain the particle size of the flake graphite in the negative electrode. Finally, following the above steps, each of the ten negative electrode sheets is tested individually, and the particle sizes of the ten electrodes are averaged to obtain the aforementioned particle size of the flake graphite.

[0096] In some embodiments, the degree of graphitization of the flake graphite is 91%-98%. Exemplarily, the degree of graphitization of the flake graphite can be typical but not limiting values ​​such as 91%, 92%, 93%, 94%, 95%, 98%.

[0097] When the degree of graphitization of flake graphite is within the above range, its flexibility is good. This allows flake graphite to effectively absorb and disperse stress when the volume change of silicon-based materials during charging and discharging, resulting in a more balanced stress distribution inside the negative electrode sheet. This reduces the risk of excessive stress accumulation in local areas, greatly improves the stability of the negative electrode sheet, and thus effectively extends the cycle life of the battery.

[0098] For the (002) crystal plane of graphite, the interlayer spacing d 002 The Lerf-Kaiser formula is typically used to convert between graphitization degree G and graphitization degree G.

[0099]

[0100] Where 0.3440 and 0.3354 are empirical constants in nm, representing the (002) interplanar spacing of completely amorphous carbon and ideal graphite, respectively.

[0101] For example, the graphitization degree of flake graphite is in the range of 91% to 95%. Calculations using the Lerf-Kaiser formula show that the interlayer spacing of the (002) crystal planes of this flake graphite ranges from 0.3358 nm to 0.3362 nm.

[0102] Therefore, the graphitization degree of flake graphite falls within the aforementioned range, resulting in a relatively large interlayer spacing. On one hand, this larger interlayer spacing provides a stable and efficient transport channel for the rapid insertion and extraction of active ions. During battery charging and discharging, ions can rapidly insert and extract, significantly improving ion transport efficiency. This effectively accelerates the battery's charging and discharging rate, drastically shortens charging time, and enables the battery to exhibit excellent fast-charging performance. On the other hand, the larger interlayer spacing provides more ample space for relative slippage between the flake graphite layers. At this point, the energy barrier required to overcome for relative slippage is lower, making slippage easier to occur. When the battery is charging and discharging, the silicon-based material exerts a force on the flake graphite due to volume expansion. The larger interlayer spacing allows the graphite layers to smoothly slip relative to each other, effectively buffering and dispersing stress, reducing the rebound problem of the negative electrode sheet, and effectively improving the battery's cycle life.

[0103] In some embodiments, the silicon-based material includes at least one of silicon oxides, silicon-carbon composites, and silicon alloys. In some embodiments, the silicon-based material may also be a pre-lithiated silicon-based material.

[0104] In some specific examples, silicon-based materials include silicon-carbon materials, silicon-oxygen materials, or pre-lithiated silicon-oxygen particles.

[0105] In some embodiments, the mass percentage of silicon in the silicon-based material is 45%-60%.

[0106] Silicon has a high theoretical specific capacity, but it also undergoes significant volume changes during charging and discharging. Therefore, controlling the mass ratio of silicon to 45%-60% can effectively alleviate the volume expansion problem of silicon through synergistic effects with flake graphite, allowing silicon-based materials to maintain good integrity after multiple cycles and extending battery life.

[0107] In some embodiments, the specific surface area of ​​flake graphite is 10-30 m². 2 / g. For example, the BET specific surface area of ​​flake graphite can be 10m². 2 / g, 15m 2 / g、20m 2 / g、25m 2 / g、30m 2 / g and other typical but non-restrictive values.

[0108] In this application, the specific surface area can be determined by referring to GB / T 19587-2004 standard for the determination of specific surface area of ​​solid materials by gas adsorption BET method. The specific surface area is determined by nitrogen adsorption analysis and calculated by BET (Brunauer Emmett Teller) method. The specific surface area analysis can be performed by a TniStarl 3020 specific surface area and porosity analyzer from Micromeritics, USA.

[0109] Within the aforementioned range, flake graphite possesses a greater number of active sites, thus providing more surface space and active sites for electrolyte adsorption. This helps create a favorable ion conduction environment within the battery, enabling active ions to transport more smoothly between the negative electrode and the electrolyte, thereby effectively improving the battery's charge-discharge efficiency and performance stability.

[0110] In some embodiments, the first conductive agent further includes a first dotted conductive agent, wherein the mass ratio of the first dotted conductive agent to the flake graphite is 1:(1-5).

[0111] For example, the mass ratio of the first dotted conductive agent to the flake graphite can be a typical but non-limiting value such as 1:1, 1:2, 1:3, 1:4, 1:5, etc.

[0112] For example, the first dotted conductive agent includes, but is not limited to, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, and carbon dots.

[0113] The first point-like conductive agent particles can tightly fill the gaps between silicon-based material particles, forming numerous direct contact points with the silicon-based material. These contact points constitute short-range electron conduction paths, enabling rapid electron transfer between silicon-based material particles and effectively improving local electron transport efficiency.

[0114] Flake graphite has a flat, sheet-like structure with a large aspect ratio. Its large planar size allows it to span multiple silicon-based material particles and localized regions formed by the first point-like conductive agent, building mid-range electronic conduction bridges and connecting dispersed short-range electrical connection regions in series, thus achieving efficient electron transport over a larger area.

[0115] The short-range electrical connections formed by the first dot-shaped conductive agent work in conjunction with the medium-range electrical connections provided by the flake-like graphite to construct a more efficient conductive network within the negative electrode. Electrons can be transported quickly and orderly within this conductive network, significantly reducing the overall resistance of the electrode. In fast-charging scenarios, a large current can efficiently pass through this conductive network, prompting more active ions to quickly embed into the silicon-based material, significantly improving the battery's charging speed and meeting users' demands for fast charging.

[0116] In some embodiments, the first conductive agent further includes a linear conductive agent, and the mass ratio of the linear conductive agent, the first dot-shaped conductive agent and the flake graphite is 1:(4-6):(12-18).

[0117] For example, the mass ratio of the linear conductive agent, the first dotted conductive agent, and the flake graphite can be typical but not limiting values ​​such as 1:4:12, 1:4:15, 1:4:18, 1:6:18, 1:6:12, 1:6:15, and 1:5:15.

[0118] For example, linear conductive agents include at least one of carbon nanotubes, carbon nanowires, and carbon fibers.

[0119] The linear conductive agent connects the short-range region formed by the first point-like conductive agent and the medium-range region constructed by the flake-like graphite. In this way, after completing short-range and medium-range transport, electrons can quickly traverse the entire negative electrode along the linear conductive agent, achieving long-range, efficient electron transport within the negative electrode. This multi-layered electron transport path within the negative electrode significantly improves electron transport efficiency, greatly optimizes the internal reaction kinetics of the battery, and allows the battery to be efficiently charged in a short time, exhibiting excellent fast-charging performance.

[0120] Several linear conductive agents, due to their flexibility and ductility, easily interweave within the first negative electrode film, constructing a three-dimensional support network between silicon-based material particles. During charging and discharging, the silicon-based material undergoes dramatic volume expansion and contraction due to the insertion and extraction of lithium ions. At this time, the network formed by the linear conductive agents can constrain the silicon-based material particles from multiple directions, limiting excessive expansion and contraction, effectively suppressing rebound amplitude, improving the stability of the negative electrode, reducing the rate of capacity decay, and significantly extending the battery's lifespan.

[0121] In some embodiments, the first negative electrode film layer further includes a first dispersant and a first binder. Based on the total mass of the first negative electrode film layer as 100%, the content of the first negative electrode active material is 80%-85%, the content of the first conductive agent is 10%-15%, the content of the first dispersant is 1%-1.5%, and the content of the first binder is 4%-6%.

[0122] For example, the content of the first negative electrode active material can be a typical but non-limiting value such as 80%, 81%, 82%, 83%, 84%, 85%; the content of the first conductive agent can be a typical but non-limiting value such as 10%, 11%, 12%, 13%, 14%, 15%; the content of the first dispersant can be a typical but non-limiting value such as 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%; and the content of the first binder can be a typical but non-limiting value such as 4%, 4.5%, 5%, 5.5%, 6%.

[0123] For example, the first adhesive includes, but is not limited to, at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0124] For example, the first dispersant includes, but is not limited to, sodium carboxymethyl cellulose (CMC-Na).

[0125] By adjusting the content ratio of each component in the first negative electrode film layer, it is beneficial for each component to exert a synergistic effect. Specifically, the appropriate content of the first negative electrode active material helps to improve the energy density of the battery; the appropriate content of the first conductive agent can build a stable and efficient conductive network between the negative electrode active materials, greatly reducing electron transport resistance, significantly improving the battery charge and discharge rate, and meeting the fast charging requirements; an appropriate amount of the first dispersant helps the components to mix evenly and form a stable and uniform negative electrode film layer; and an appropriate amount of the first binder tightly bonds the components into a solid whole, giving the negative electrode sheet good mechanical strength, effectively reducing material shedding and pulverization, and greatly extending the battery cycle life.

[0126] In some embodiments, the negative electrode sheet further includes a second negative electrode film layer, which is disposed between the first negative electrode film layer and the negative electrode current collector;

[0127] The second negative electrode film layer includes a second negative electrode active material, which includes a carbon-based material.

[0128] During battery charging, active ions migrate from the electrolyte to the negative electrode and gradually embed themselves into the electrode material. Silicon-based materials, with their preferential lithium intercalation properties, are distributed in the first negative electrode layer, which is closer to the electrolyte. This significantly shortens the transport distance of active ions from the electrolyte to the lithium intercalation reaction sites, thereby significantly increasing the transport rate of active ions and greatly improving the battery's fast-charging performance.

[0129] The lithium intercalation process of carbon-based materials involves relatively small volume changes and good flexibility. When distributed in the second negative electrode film layer, which is the side close to the negative electrode current collector, the carbon-based material can absorb and disperse the stress through its own deformation when the first negative electrode film layer is subjected to stress due to the expansion of silicon-based materials. This reduces the overall rebound of the negative electrode sheet, minimizes performance degradation caused by structural damage, and extends the battery cycle life.

[0130] In some embodiments, the carbon-based material includes at least one of artificial graphite, natural graphite, soft carbon, and hard carbon; the morphology of the carbon-based material includes at least one of spherical, near-spherical, blocky, and sheet-like shapes.

[0131] In some embodiments, the thickness ratio of the first negative electrode film layer to the second negative electrode film layer is (0.6-1):1.

[0132] For example, the thickness ratio of the first negative electrode film layer to the second negative electrode film layer can be a typical but non-limiting value such as 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, etc.

[0133] Silicon-based materials have strong lithium intercalation capabilities but suffer from significant volume expansion. However, silicon-based materials exhibit relatively small volume changes during lithium intercalation and possess good conductivity and structural stability. Therefore, placing silicon-based materials in the first negative electrode layer near the electrolyte and carbon-based materials in the second negative electrode layer near the current collector fully utilizes the high specific capacity of silicon-based materials, enabling rapid intercalation of a large number of lithium ions during charging, thus improving the battery's charging speed and overall capacity. Furthermore, a second negative electrode layer of appropriate thickness provides a stable transport channel for lithium ion extraction and transport during discharge, promoting rapid electron transport and thereby enhancing the battery's charge and discharge efficiency.

[0134] In some embodiments, the second negative electrode film layer further includes a second conductive agent, a second dispersant, and a second binder. Based on the total mass of the second negative electrode film layer (100%), the content of the second negative electrode active material is 95%-97%, the content of the second conductive agent is 0.5%-1%, the content of the second dispersant is 1%-1.5%, and the content of the second binder is 2%-4%.

[0135] For example, the content of the second negative electrode active material can be typical but not limiting values ​​such as 95%, 95.5%, 96%, 97%; the content of the second conductive agent can be typical but not limiting values ​​such as 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%; the content of the second dispersant can be typical but not limiting values ​​such as 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%; and the content of the second binder can be typical but not limiting values ​​such as 2%, 2.5%, 3%, 3.5%, 4%.

[0136] For example, the second adhesive includes, but is not limited to, at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0137] For example, the second dispersant includes, but is not limited to, sodium carboxymethyl cellulose (CMC-Na).

[0138] By adjusting the content ratio of each component in the second negative electrode film, it is beneficial for each component to exert a synergistic effect. An appropriate amount of second negative electrode active material can stably store active ions and provide structural support; an appropriate amount of second conductive agent can build a highly efficient conductive network, accelerate electron conduction, and improve charge and discharge rates; an appropriate amount of second dispersant promotes the uniform distribution of each component, optimizes slurry performance and coating quality; and an appropriate proportion of second binder firmly binds the other components, enhances the mechanical strength of the negative electrode sheet, improves the structural stability of the negative electrode sheet during charge and discharge, and improves battery cycle performance and fast charging performance.

[0139] In some embodiments, the second conductive agent includes a second dot-shaped conductive agent.

[0140] For example, the second dotted conductive agent includes, but is not limited to, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, and carbon dots.

[0141] The second point-like conductive agent can effectively fill the gaps between carbon-based material particles, thereby forming a good conductive path between the carbon-based materials and effectively reducing the overall resistance of the negative electrode. This makes the transfer of electrons within the negative electrode more efficient, significantly improving the battery's charge and discharge efficiency and enhancing its fast-charging performance.

[0142] In some embodiments, the film resistance of the negative electrode is 0.002Ω-0.01Ω.

[0143] For example, the film resistance of the negative electrode can be a typical but non-limiting value such as 0.002Ω, 0.004Ω, 0.006Ω, 0.008Ω, or 0.01Ω.

[0144] When the film resistance of the negative electrode is within the above range, the current encounters less resistance when it is transmitted through the electrode, which improves the charging and discharging efficiency and energy utilization of the battery. Moreover, the lower film resistance is more conducive to the charging and discharging of individual battery cells under high current conditions, which can meet the needs of equipment for fast charging and high power output. At the same time, it also helps to reduce the polarization phenomenon of the battery during high current charging and discharging, thus extending the battery life.

[0145] Typically, a battery cell includes a positive electrode, a negative electrode, an electrolyte, and a separator. During charging and discharging, active ions move back and forth between the positive and negative electrodes, inserting and releasing. The electrolyte acts as a conductor of ions between the positive and negative electrodes. The separator, positioned between the positive and negative electrodes, primarily prevents short circuits while allowing ions to pass through.

[0146] [Positive electrode plate]

[0147] The positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one surface of the positive current collector, the positive electrode film layer containing a positive active material. As an example, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive current collector.

[0148] This application does not impose any particular limitation on the positive electrode current collector, as long as it achieves the purpose of this application. In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector can be obtained by forming a metal material on a polymer material substrate. The composite current collector can be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.

[0149] In some embodiments, the positive electrode film contains a positive electrode active material, which may include positive electrode active materials known in the art for use in batteries. As an example, the positive electrode active material of a lithium-ion secondary battery may include at least one of the following materials: olivine-structured lithium-containing phosphates, lithium transition non-aluminum metal oxides, and their respective modified compounds. However, this application is not limited to these materials, and other conventional materials that can be used as battery positive electrode active materials may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition non-aluminum metal oxides include, but are not limited to, at least one of lithium cobalt oxide, nickel-cobalt-manganese ternary materials, nickel-cobalt-aluminum ternary materials, nickel-cobalt-manganese-aluminum quaternary materials, lithium iron phosphate, lithium manganese phosphate, lithium vanadium phosphate, lithium manganese oxide, and their modified compounds. Examples of olivine-structured lithium-containing phosphates include, but are not limited to, at least one of lithium iron phosphate, lithium iron phosphate and carbon composites, lithium manganese phosphate, lithium manganese phosphate and carbon composites, lithium iron manganese phosphate, and lithium iron manganese phosphate and carbon composites. Based on the total weight of the positive electrode film, the weight ratio of the positive electrode active material in the positive electrode film is 80%-100%.

[0150] In some embodiments, the positive electrode film layer may optionally include a binder. As an example, the binder in the positive electrode film layer may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resins. Based on the total weight of the positive electrode film layer, the weight percentage of the binder in the positive electrode film layer is 0%-20%.

[0151] In some embodiments, the positive electrode film may optionally include a conductive agent. As an example, the conductive agent in the positive electrode film may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. The conductive agent accounts for 0%-20% of the total weight of the positive electrode film.

[0152] In some embodiments, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive active material, conductive agent, binder and any other components, in a solvent (e.g. N-methylpyrrolidone) to form a positive electrode slurry, coating the positive electrode slurry on the surface of the positive current collector, drying it and then cold pressing it through a cold rolling mill to form the positive electrode sheet.

[0153] [Negative electrode plate]

[0154] The negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector. As an example, the negative current collector has two surfaces opposite each other in its own thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative current collector.

[0155] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may be a polymer matrix material and a metal layer formed on at least one surface of the polymer matrix material. The composite current collector may be formed on the surface of the polymer matrix material using copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, or silver alloys. The polymer matrix material may be one or more of the following substrates: polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0156] In some embodiments, the negative electrode film layer includes only a first negative electrode film layer, which includes a first negative electrode active material, and the first negative electrode active material includes a silicon-based material. The silicon-based material may include one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. In some specific examples, the silicon-based material is a silicon oxide material, pre-lithiated silicon oxide particles, or a silicon-carbon material.

[0157] In some embodiments, the first negative electrode film layer further includes a first conductive agent, which includes flake graphite. In some specific examples, the first conductive agent may also include a first particulate conductive agent and a linear conductive agent.

[0158] In some embodiments, the first negative electrode film layer may also optionally include other additives, such as dispersants (e.g., sodium carboxymethyl cellulose (CMC-Na)).

[0159] In some embodiments, the first negative electrode film layer may optionally include a first binder.

[0160] In some embodiments, the negative electrode film layer includes a first negative electrode film layer and a second negative electrode film layer, wherein the second negative electrode film layer is disposed between the first negative electrode film layer and the negative electrode current collector. The second negative electrode film layer includes a second negative electrode active material, which includes a carbon-based material. In some specific examples, the carbon-based material includes one or more of graphite, soft carbon, hard carbon, and composite materials obtained by coating modification of the above materials. The morphology of the carbon-based material includes one or more of spherical, near-spherical, blocky, and sheet-like shapes.

[0161] In some embodiments, the second negative electrode film may optionally include other additives, such as dispersants (e.g., sodium carboxymethyl cellulose (CMC-Na)).

[0162] In some embodiments, the second negative electrode film layer may optionally include a second binder.

[0163] In some embodiments, the negative electrode sheet can be prepared by dispersing the above-mentioned components for preparing the negative electrode sheet, such as negative electrode active material, conductive agent, binder and any other components, in a solvent (a non-limiting example of a solvent is deionized water) to form a negative electrode slurry; coating the negative electrode slurry on at least one side surface of the negative electrode current collector, and obtaining the negative electrode sheet after drying, cold pressing and other processes.

[0164] When the negative electrode sheet only includes the first negative electrode film layer, the first negative electrode active material, the first conductive agent, the first binder and any other components are dispersed in a solvent (a non-limiting example of a solvent is deionized water) to form a first slurry, which is coated on the negative electrode current collector and then subjected to drying, cold pressing and other processes to obtain the negative electrode sheet.

[0165] When the negative electrode sheet includes a first negative electrode film layer and a second negative electrode film layer, a second slurry (a second negative electrode active material, a second conductive agent, a second binder, and any other components dispersed in a solvent to form a second slurry) is coated onto the negative electrode current collector and dried to form a second negative electrode film layer on the negative electrode current collector. Then, the first slurry (a first negative electrode active material, a first conductive agent, a first binder, and any other components dispersed in a solvent to form a first slurry) is coated onto the second negative electrode film layer to form a first negative electrode film layer, dried, and then cold-pressed, edge-trimmed, slit, and cut into sheets to obtain the negative electrode sheet.

[0166] [Electrolytes]

[0167] The electrolyte acts as a conductor of ions between the positive and negative electrodes. This application does not impose specific limitations on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid, gel-like, or entirely solid.

[0168] In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent.

[0169] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium fluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, lithium tetrafluorooxalate phosphate, N-dialkylpyrrolidine onium lithium salt, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, and N-ethylpyrrolidine onium lithium tetrafluoroborate.

[0170] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.

[0171] [Isolation membrane]

[0172] This application does not impose any particular restrictions on the type of separator membrane; any known porous separator membrane with good chemical and mechanical stability can be selected.

[0173] In some embodiments, the material of the separator can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0174] In some embodiments, the thickness of the separator is 6 μm to 40 μm, and optionally 12 μm to 20 μm.

[0175] In some embodiments, the positive electrode sheet, separator, and negative electrode sheet can be formed into an electrode assembly through a winding or stacking process. The electrode assembly is then placed in an outer package, dried, and injected with electrolyte. After vacuum sealing, settling, formation, and shaping processes, a battery cell is obtained. The shape of the battery cell is not particularly limited; it can be cylindrical, square, or any other arbitrary shape.

[0176] In some embodiments, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly by a winding process or a stacking process.

[0177] In some embodiments, the battery cell may include an outer packaging. This outer packaging may be used to encapsulate the electrode assembly and electrolyte described above.

[0178] In some embodiments, the outer packaging of the battery cell can be a rigid shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell can also be a flexible package, such as a pouch-type flexible package. The material of the flexible package can be plastic; further, non-limiting examples of plastic may include one or more of polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0179] The following description, with appropriate reference to the accompanying drawings, describes the battery cell, battery device, and power-consuming device provided in the embodiments of this application.

[0180] Figure 1 This is an exploded view of a battery device 100 as an example. The battery device 100 includes a housing 10 and battery cell assemblies 20, with the battery cell assemblies 20 housed within the housing 10. The housing 10 provides a space for housing the battery cell assemblies 20 and can have various structures. In some embodiments, the housing 10 may include a first housing 11 and a second housing 12, which overlap each other, collectively defining a closed space for housing the battery cell assemblies 20. Of course, the housing 10 formed by the first housing 11 and the second housing 12 can have various shapes, such as a cylinder, a cuboid, etc. Multiple battery cell assemblies 20 can be arranged in any manner within the battery housing.

[0181] In the battery device 100, there can be one or more battery cell components 20. Multiple battery cell components 20 can be connected in series, parallel, or in a mixed manner. A mixed connection means that multiple battery cell components 20 are connected in both series and parallel. Multiple battery cell components 20 can be directly connected in series, parallel, or in a mixed manner, and then the whole formed by multiple battery cell components 20 is housed in the housing 10. Of course, the battery device 100 can also be formed by first connecting multiple battery cell components 20 in series, parallel, or in a mixed manner to form a battery module, such as a battery module or battery pack. Multiple battery modules are then connected in series, parallel, or in a mixed manner to form a whole and housed in the housing 10.

[0182] Battery cell assembly 20 includes multiple battery cells 30. Figure 2 This is an exploded view of a single battery cell 30 as an example. The single battery cell 30 includes a housing 31, a cover plate 33, an electrode assembly 32, and other functional components.

[0183] The housing 31 may include a base plate and side plates connected to the base plate, the base plate and side plates forming a receiving cavity. The housing 31 is a hollow structure with an opening at one end, and the housing 31 is used to cooperate with the cover plate 33 to form an internal environment for accommodating the electrode assembly 32, electrolyte, and other functional components. The housing 31 can be of various shapes and sizes, such as cuboid, cylindrical, hexagonal prism, etc. Specifically, the shape of the housing 31 can be determined according to the specific shape and size of the electrode assembly 32. The material of the housing 31 can be, but is not limited to, copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc., and is not limited here. The cover plate 33 is a component that covers the opening of the housing 31 to isolate the internal environment of the battery cell 30 from the external environment. The material of the cover plate 33 can be, but is not limited to, copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc., and is not limited here.

[0184] Figure 3 This is a schematic diagram of an example electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the device's requirements for high power and high energy density, a battery pack or battery module can be used.

[0185] Example

[0186] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.

[0187] Example 1

[0188] This application provides a single battery cell.

[0189] [Preparation of the negative electrode sheet]

[0190] The negative electrode sheet includes a negative current collector and a negative electrode film layer, with a negative electrode film layer disposed on both sides of the negative current collector. The negative electrode film layer includes a first negative electrode film layer and a second negative electrode film layer, with the second negative electrode film layer disposed between the first negative electrode film layer and the negative electrode film layer.

[0191] The thickness ratio of the first negative electrode film to the second negative electrode film is 1:1, wherein the thickness of the first negative electrode film is 60 μm and the thickness of the second negative electrode film is 60 μm.

[0192] The first negative electrode film layer comprises a first negative electrode active material (selected from silicon-carbon materials, with a particle size of 10 μm) in a mass ratio of 82:12:1:5, a first conductive agent, a first dispersant (selected from sodium carboxymethyl cellulose), and a first binder (selected from styrene-butadiene rubber). The first conductive agent comprises a linear conductive agent (selected from carbon nanotubes), a first dot-like conductive agent (selected from carbon black), and flake graphite in a mass ratio of 1:5:15. The flake graphite has the following specifications: a particle size of 5 μm, an aspect ratio of 10, and a graphitization degree of 91%.

[0193] The second negative electrode film layer comprises a second negative electrode active material (selected from artificial graphite or granules), a second conductive agent (selected from carbon black), a second dispersant (selected from sodium carboxymethyl cellulose), and a second binder (selected from styrene-butadiene rubber) in a mass ratio of 96.5:0.5:1:2.

[0194] The method for preparing the negative electrode sheet includes the following steps:

[0195] Step 1: Add the second negative electrode active material, the second conductive agent, the second dispersant, and the second binder to deionized water in the above proportions, stir and mix evenly to prepare the second negative electrode slurry (solid content of 45%).

[0196] Step 2: Coat the two surfaces of the negative electrode current collector with the second negative electrode slurry and dry it at a temperature of 85°C to form the second negative electrode film layer.

[0197] Step 3: Add the first negative electrode active material, the first conductive agent, the first dispersant and the first binder to deionized water in the above proportions, stir and mix evenly to prepare the first negative electrode slurry (solid content of 45%).

[0198] Step 4: Coat the first negative electrode slurry onto the surface of the second negative electrode film layer away from the negative electrode current collector, dry it at a temperature of 110°C to form the first negative electrode film layer, and then perform cold pressing (cold pressing pressure of 20MPa), slitting, and cutting to obtain the negative electrode sheet.

[0199] [Preparation of the positive electrode sheet]

[0200] The positive electrode active material, nickel-cobalt-manganese ternary material (NCM811), conductive agent carbon black, and binder PVDF (polyvinylidene fluoride) were mixed in a mass ratio of 98:1:1. N-methylpyrrolidone (NMP) solvent was added, and the mixture was stirred for 6 hours to obtain a positive electrode slurry (solid content of 50 wt%). The positive electrode slurry was uniformly coated on both sides of the positive electrode current collector aluminum foil (thickness of 13 μm), and then dried and cold-pressed to form a positive electrode film layer with a thickness of 35 μm, thus obtaining the positive electrode sheet.

[0201] [Isolation membrane]

[0202] Separator: A polyethylene film (PE) with a thickness of 7μm is used as the separator.

[0203] Electrolyte

[0204] Ethylene carbonate (EC), diethyl carbonate (DMC), and methyl ethyl carbonate (EMC) were mixed in a volume ratio of 33:33:34. Then, the electrolyte salt LiPF6 was uniformly dissolved in the above mixed solvent to obtain an electrolyte solution with a lithium salt concentration of 1 mol / L.

[0205] Preparation of battery cells: The electrode assembly is obtained by placing and winding the electrode in the order of "separator-negative electrode-separator-positive electrode"; the electrode assembly is placed in the outer packaging (aluminum-plastic film bag), electrolyte is injected, and after vacuum sealing and standing for 6 hours, the battery cell is obtained.

[0206] Example 2

[0207] This application provides a battery cell that differs from Embodiment 1 in that the negative electrode sheet is different. Specifically, the scale-like graphite contained in the first negative electrode film layer has different specifications: the scale-like graphite has a Dv50 particle size of 5μm, an aspect ratio of 80, and a graphitization degree of 91%.

[0208] Example 3

[0209] This application provides a battery cell that differs from Embodiment 1 in that the negative electrode sheet is different. Specifically, the scale-like graphite contained in the first negative electrode film layer has different specifications: the scale-like graphite has a Dv50 particle size of 5μm, an aspect ratio of 150, and a graphitization degree of 91%.

[0210] Example 4

[0211] This application provides a battery cell that differs from Embodiment 1 in that the negative electrode sheet is different. Specifically, the specifications of the flake graphite contained in the first negative electrode film layer are different. The specifications of the flake graphite are: Dv50 particle size of 5μm, aspect ratio of 160, and graphitization degree of 91%.

[0212] Example 5

[0213] This application provides a battery cell that differs from Embodiment 1 in that the negative electrode sheet is different. Specifically, the graphitization degree of the flake graphite contained in the first negative electrode film layer is 95%.

[0214] Example 6

[0215] This application provides a battery cell that differs from Embodiment 1 in that the negative electrode sheet is different. Specifically, the graphitization degree of the flake graphite contained in the first negative electrode film layer is 98%.

[0216] Example 7

[0217] This application provides a battery cell that differs from Embodiment 1 in that the negative electrode sheet is different. Specifically, the graphitization degree of the flake graphite contained in the first negative electrode film layer is 88%.

[0218] Example 8

[0219] This application provides a battery cell that differs from Embodiment 1 in that the negative electrode sheet is different. Specifically, the silicon-carbon material contained in the first negative electrode film has a particle size of 10 μm, and the flake graphite contained therein has a particle size of 8 μm.

[0220] Example 9

[0221] This application provides a battery cell that differs from Embodiment 1 in that the negative electrode sheet is different. Specifically, the silicon-carbon material contained in the first negative electrode film has a particle size of 7 μm, and the flake graphite contained therein has a particle size of 4 μm.

[0222] Example 10

[0223] This application provides a battery cell that differs from Embodiment 1 in that the negative electrode sheet is different. Specifically, the thickness ratio of the first negative electrode film to the second negative electrode film is 0.6:1, wherein the thickness of the first negative electrode film is 45 μm and the thickness of the second negative electrode film is 75 μm.

[0224] Example 11

[0225] This application provides a battery cell that differs from Embodiment 1 in that the negative electrode sheet is different. Specifically, the first conductive agent in the first negative electrode film layer includes a first dotted conductive agent (selected from carbon black) and flake graphite in a mass ratio of 5:15.

[0226] Example 12

[0227] This application provides a battery cell that differs from Embodiment 1 in that the negative electrode sheet is different. Specifically, the first conductive agent contained in the first negative electrode film layer is only flake graphite, and the specifications of the flake graphite are: Dv50 particle size of 5μm, aspect ratio of 10, and graphitization degree of 91%.

[0228] Comparative Example 1

[0229] This comparative example provides a single battery cell, which differs from Example 1 in that the negative electrode sheet is different. Specifically, the first conductive agent in the first negative electrode film layer is only the first dot-shaped conductive agent (carbon black).

[0230] Comparative Example 2

[0231] This comparative example provides a battery cell that differs from Example 1 in that the negative electrode sheet is different. Specifically, the first conductive agent in the first negative electrode film layer includes a linear conductive agent (selected from carbon nanotubes) and a first dotted conductive agent (selected from carbon black) in a mass ratio of 1:5.

[0232] Comparative Example 3

[0233] This comparative example provides a battery cell that differs from Example 1 in that the negative electrode sheet is different. Specifically, the specifications of the flake graphite contained in the first negative electrode film layer are different. The specifications of the flake graphite are: a particle size of 5 μm, an aspect ratio of 5, and a graphitization degree of 91%.

[0234] Performance testing

[0235] (1) Microscopic morphology

[0236] The flake-like graphite provided in Example 1 was tested using a scanning electron microscope (SEM), and the results are as follows: Figure 4 As shown. From Figure 4 It is clearly visible that the flake graphite exhibits a regular and flat sheet-like shape, with clear sheet outlines and neat edges. The sheet surface is relatively smooth, which helps to reduce interfacial resistance and enhance the adhesion between the two when combined with silicon-carbon materials.

[0237] The negative electrode sheet provided in Example 1 was processed using an ion polisher (IB-09010CP) to obtain a cross-section of the negative electrode sheet along its thickness direction. Background scattering of this cross-section was performed using a scanning electron microscope (ZEISSSEM (Sigma-02-33) (0.1-30KV)). The results are as follows: Figure 5 .from Figure 5In the background scattering field of view, it is immediately apparent that silicon-based materials scatter electrons more effectively than carbon-based materials, resulting in a significantly brighter color. Further observation reveals that the brighter silicon-based material areas are mainly concentrated in the outer layer, the first anode film, distributed in continuous or semi-continuous blocky or granular forms. The relatively darker carbon-based material areas are located in the inner second anode film, tightly adhering to the anode current collector. Focusing on the first anode film, the distribution of flake-like graphite is clearly discernible, well-interspersed among the silicon particles.

[0238] The negative electrode sheet (cold-pressed negative electrode sheet) provided in Comparative Example 1 was tested using a scanning electron microscope (SEM), such as... Figure 6 As shown. From Figure 6 It can be clearly seen that after cold pressing, the silicon-based material particles are obviously broken, with a large number of particles showing cracks, and some even breaking into small pieces.

[0239] The negative electrode sheet (cold-pressed negative electrode sheet) provided in Example 1 was tested using a scanning electron microscope (SEM), such as... Figure 7 As shown. From Figure 7 As can be seen, the degree of fragmentation of silicon-based materials is significantly reduced. Most silicon-based material particles maintain a relatively intact shape with clear outlines, which is quite different from the fragmentation of silicon-based material particles in Comparative Example 1.

[0240] (2) Fast charging performance test

[0241] At 25°C, the battery cell was charged at a constant current of 0.33C to the charging cutoff voltage of 3.8V, then charged at a constant voltage to a current of 0.05C, left to stand for 5 minutes, and then discharged at a constant current of 0.33C to the discharge cutoff voltage of 2.0V. Its actual capacity was recorded as C0.

[0242] Then, the battery was sequentially charged at a constant current of 0.5C0, 1C0, 1.5C0, 2C0, 2.5C0, 3C0, 3.5C0, 4C0, 4.5C0, and 5C0 until the full battery charging cutoff voltage of 3.8V or the negative terminal cutoff potential of 0V (whichever comes first). After each charging, it was discharged at 1C0 until the full battery discharge cutoff voltage of 2.0V. The charging rates were recorded at 10%, 20%, 30%, 40%, 50%, 60%, 70%, and 80% SOC (State of Charge). The negative electrode potential corresponding to the state of charge (SOC) is plotted at different rates. After linear fitting, the charging rate corresponding to the negative electrode potential of 0V under different SOC states is obtained. This charging rate is the charging window under that SOC state, denoted as C10%SOC, C20%SOC, C30%SOC, C40%SOC, C50%SOC, C60%SOC, C70%SOC, and C80%SOC. According to the formula: (60 / C20%SOC+60 / C30%SOC+60 / C40%SOC+60 / C50%SOC+60 / C60%SOC+60 / C70%SOC+60 / C80%SOC)×10%, the charging time T of the battery from 10%SOC to 80%SOC is calculated. The shorter the charging time T, the better the fast charging performance of the battery cell.

[0243] The charging curves of Example 1 and Comparative Example 1 under different SOC states during the above test process are shown below. Figure 8 As shown. In Figure 8 In the graph, the vertical axis represents the charging rate (Rate, C), and the horizontal axis represents the state of charge (SOC). A direct analysis of this graph reveals that, compared to Comparative Example 1, the battery provided in Example 1 exhibits a significant advantage in charging rate. At a SOC greater than 20%, it can achieve a higher charging rate, demonstrating superior fast-charging performance.

[0244] (3) Cyclic performance test

[0245] At 25℃, the battery cell was charged at 0.33C to the upper limit cutoff voltage of 4.25V, then charged at a constant voltage of 4.25V to 0.05C, allowed to stand for 30 minutes, and then discharged at a current of 0.33C to the lower limit voltage of 2.5V. This cycle was repeated 3 times, and the cell capacity Cn of the last discharge was recorded. Next, the battery cell was discharged at a constant current of 0.5Cn to the lower limit voltage of 2.5V, allowed to stand for 10 minutes, and then charged at a constant current of 0.04Cn to 0.97Cn. After standing for 30 minutes, the cell capacity was recorded. After resting, the voltage value V1 is recorded. Then, the battery is discharged at a constant current of 0.5Cn to 0.92Cn, and the discharge end voltage V2 is recorded. The battery is discharged at a constant current of 0.5Cn to the lower limit voltage of 2.5V. After resting for 2 hours, it is charged at a constant current of 0.5Cn to V1, and then charged at a constant voltage of V1 to 0.05Cn. After resting for 10 minutes, it is discharged at a current of 0.5Cn to V2. This process is repeated, and one charge-discharge cycle is one complete cycle until the battery capacity is less than 80% of the initial capacity. The number of cycles Cy is recorded.

[0246] (4) Detection of lithium plating in cycles

[0247] After completing the above cycle performance tests, batteries that had undergone cyclic charge-discharge cycles until their capacity was less than 80% of their initial capacity were fully charged. Once fully charged, the batteries were disassembled to observe the lithium plating on the negative electrode.

[0248] (5) In-situ rebound test

[0249] The thickness of the negative electrode sheet during the preparation of a single battery cell is measured using a micrometer. That is, the thickness of the negative electrode sheet after cold pressing is denoted as H0.

[0250] The battery cell is placed in an in-situ rebound tester and charged and discharged in constant force mode. The cell thickness / expansion force is monitored in situ as a function of SOC. The thickness of the negative electrode plate when the battery reaches 100 SOC is recorded and denoted as H1.

[0251] The in-situ rebound rate is calculated using formula (I).

[0252]

[0253] The relevant parameters of the negative electrode sheet in the battery cells provided in Examples 1-12 and Comparative Examples 1-3 are shown in Table 1.

[0254] Table 1

[0255]

[0256] In Table 1:

[0257] The mass ratio refers to the mass ratio of linear conductive agent, first dot conductive agent, and flake graphite;

[0258] The thickness ratio refers to the ratio of the thickness of the first negative electrode film layer to the thickness of the second negative electrode film layer.

[0259] The performance parameters of the battery cells provided in Examples 1-12 and Comparative Examples 1-3 are shown in Table 2.

[0260] Table 2

[0261] Charging time (min) Number of cycles Lithium plating In-situ rebound rate (%) Example 1 16.7 680 Non-lithium plating 86% Example 2 16.6 770 Non-lithium plating 81% Example 3 16.4 930 Non-lithium plating 71% Example 4 16.3 950 Non-lithium plating 69% Example 5 16.3 750 Non-lithium plating 82% Example 6 16.1 810 Non-lithium plating 77% Example 7 16.7 650 Non-lithium plating 88% Example 8 17.1 710 Non-lithium plating 89% Example 9 16.0 630 Non-lithium plating 79% Example 10 16.8 620 Non-lithium plating 87% Example 11 17.0 640 Non-lithium plating 90% Example 12 17.2 660 Non-lithium plating 88% Comparative Example 1 19.8 400 Lithium plating 120% Comparative Example 2 18.9 450 Lithium plating 102% Comparative Example 3 17.4 610 Non-lithium plating 93%

[0262] As clearly shown in Table 2, the battery cell provided in this embodiment exhibits significant performance advantages compared to the comparative example. The cycle life of this battery cell is significantly extended, with a significantly higher number of cycles than the comparative example, and no lithium plating occurs throughout the entire operation. Simultaneously, its rebound effect is significantly weakened, and the in-situ rebound rate is significantly reduced, thereby improving battery stability. Furthermore, the battery charging time is also significantly shortened, greatly enhancing its fast-charging performance.

[0263] As can be seen from Examples 1-4 and Comparative Example 1, with the increase of the aspect ratio of flake graphite, the charging time of the battery cell gradually shortens, the number of cycles gradually increases, and the in-situ rebound rate continues to decrease. This is because the increase in aspect ratio allows the flake graphite to more fully utilize its interlayer slip properties, thereby effectively suppressing the expansion of silicon-based materials during charging and discharging.

[0264] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and not to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. These modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application, and they should all be covered within the scope of the claims and specification of this application. In particular, as long as there is no structural conflict, the various technical features mentioned in the embodiments can be combined in any way. This application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.

Claims

1. A battery cell, characterized in that, The device includes a negative electrode sheet, which includes a negative current collector and a first negative electrode film layer disposed on at least one side of the negative current collector. The first negative electrode film layer includes a first negative electrode active material and a first conductive agent. The first negative electrode active material includes a silicon-based material, and the first conductive agent includes flake graphite, wherein the aspect ratio of the flake graphite is greater than or equal to 10.

2. The battery cell as described in claim 1, characterized in that, The aspect ratio of the flake graphite is 10-160.

3. The battery cell according to any one of claims 1 to 2, characterized in that, The ratio of the particle size of the silicon-based material to the particle size of the flake graphite is 1:x, where 0.5 ≤ x < 1.

4. The battery cell according to any one of claims 1 to 3, characterized in that, The silicon-based material has a particle size of 7μm-10μm, and the flake graphite has a particle size of 4μm-8μm.

5. The battery cell according to any one of claims 1 to 4, characterized in that, The degree of graphitization of the flake graphite is 91%-98%.

6. The battery cell according to any one of claims 1 to 5, characterized in that, The silicon-based material includes at least one of silicon oxides, silicon-carbon composites, and silicon alloys; and / or, In the silicon-based material, the mass percentage of silicon is 45%-60%.

7. The battery cell according to any one of claims 1 to 6, characterized in that, The first conductive agent further includes a first dot-shaped conductive agent, wherein the mass ratio of the first dot-shaped conductive agent to the flake graphite is 1:(1-5).

8. The battery cell as described in claim 7, characterized in that, The first conductive agent further includes a linear conductive agent, and the mass ratio of the linear conductive agent, the first dotted conductive agent and the flake graphite is 1:(4-6):(12-18).

9. The battery cell as described in claim 8, characterized in that, The linear conductive agent includes at least one of carbon nanotubes and carbon fibers; and / or, The first dotted conductive agent includes at least one of carbon black, superconducting carbon, acetylene black, Ketjen black, and carbon dots.

10. The battery cell according to any one of claims 1 to 9, characterized in that, The first negative electrode film layer further includes a first dispersant and a first binder. Based on the total mass of the first negative electrode film layer as 100%, the content of the first negative electrode active material is 80%-85%, the content of the first conductive agent is 10%-15%, the content of the first dispersant is 1%-1.5%, and the content of the first binder is 4%-6%.

11. The battery cell according to any one of claims 1 to 10, characterized in that, The negative electrode sheet further includes a second negative electrode film layer, which is disposed between the first negative electrode film layer and the negative electrode current collector; the second negative electrode film layer includes a second negative electrode active material, which includes a carbon-based material.

12. The battery cell as described in claim 11, characterized in that, The thickness ratio of the first negative electrode film layer to the second negative electrode film layer is (0.6-1):

1.

13. The battery cell as described in claim 11 or 12, characterized in that, The second negative electrode film layer further includes a second conductive agent, a second dispersant, and a second binder. Based on the total mass of the second negative electrode film layer as 100%, the content of the second negative electrode active material is 95%-97%, the content of the second conductive agent is 0.5%-1%, the content of the second dispersant is 1%-1.5%, and the content of the second binder is 2%-4%.

14. The battery cell as described in claim 13, characterized in that, The second conductive agent includes a second dot-shaped conductive agent.

15. The battery cell according to any one of claims 1 to 14, characterized in that, The film resistance of the negative electrode is 0.002Ω-0.01Ω.

16. A battery device, characterized in that, Includes the battery cell as described in any one of claims 1-15.

17. An electrical device, characterized in that, Includes the battery cell as described in any one of claims 1-15 or the battery device as described in claim 16.